Iterative decision-feedback differential demodulation of bit-interleaved coded MDPSK for flat Rayleigh fading channels. - Lampe, L.H.-J.
A simple receiver structure previously proposed by the authors for convolutional coded M-ary differential phase-shift keying transmission over flat Rayleigh fading channels without channel state information is analyzed in detail. We present a thorough discussion of the iterative decoding procedure, which is referred to as iterative decision-feedback differential demodulation (iterative DF-DM). The convergence behavior of iterative DF-DM is theoretically examined. The analysis supports the observation that the iterative decoding scheme works well for target bit-error rates which are usually of interest. Furthermore, the associated cut-off rate for error-free decision feedback is studied. Judging from this performance parameter, remarkable gains in power efficiency compared to conventional differential demodulation are indicated, while the computational complexity of the decoding remains low. The results from information theory are in good agreement with the given simulation results
Keywords: Viterbi decoder; Bit-error rates; Bit-interleaved coded MDPSK; Computational complexity; Convergence behavior; Convolutional coded MDPSK; Cut-off rate; Error-free decision feedback; Flat Rayleigh fading channels; Information theory; Iterative decision-feedback differential demodulation; Iterative decoding; Performance parameter; Power efficiency; Receiver structure; Simulation results